Return on character : the real reason leaders and their companies win - Kiel, Fred (Boston, Massachusetts : Harvard Business Review Press, 2015)
"In 2001, Jim Collins published research findings that identified the "blend of personal humility and professional will" that enabled the Level 5 Leader to drive an otherwise unremarkable organization to greatness. Now, in Return on Character, Fred Kiel offers us the findings of a new study that tell us how to grow and develop that kind of extraordinary leadership. This groundbreaking book is based on Kiel's seven years of rigorous research into the "black box" that contains the little understood connection between character, leadership excellence, and organizational results. Grounded by nearly 9,000 employee observations on CEOs and their teams, Kiel offers solid evidence that character matters-leaders of strong character in his study achieved up to five times the ROA for their organizations than did leaders of weak character. Most people want to believe that good character wins, but many hard-nosed executives and analysts are skeptical on that point. Kiel's evidence not only draws a hard and direct link between strong character and strong business results, his findings go on to identify the specific character habits of exceptional leadership and how they play a role in shaping every facet of the organization. Strong morals and good character aren't mere "icing on the cake"; in Return on Character we learn how they are the primary ingredients in the decision-making processes that result in smart strategies, an innovative business model, and an engaged workforce. Return on Character definitively reports a consistent, observable relationship between high character leaders and better business results. Crucially, the book also proves that anyone can build character-whether you're a current leader or an aspiring one-it's a habit that is developed and nurtured. The book offers a methodology you can use - with ideas and advice for assessing your own habits of character, along with solid techniques for improving them, as we simultaneously "unlearn" the habits that weaken our character-and our leadership model. So whether you're leading a large organization, a small business, or any group trying to reach an important goal, this book is a guide to help you drive success"--
"What does it mean to have character as a business leader, and how does this lead to company success? Many have given partial answers to these questions, but very few have gone beyond individual stories to attempt a rigorous, research-based account of what really constitutes character and how it translates to performance. Leadership author and adviser Fred Kiel provides a fascinating and useful breakdown of the elements of character; how they are formed and how character is different from emotional intelligence and personality; and then an illuminating picture of how character fits into a larger "CEO value chain" necessary for success"--
Includes bibliographical references and index.
Keywords: Leadership; Character; Executive ability; Management -- Psychological aspects; Success in business